DOCKING-CALCULATION-BASED METHOD FOR PREDICTING PROTEIN-RNA INTERACTIONS - AKIYAMA, YUTAKA; OHUE, MASAHITO; MATSUZAKI, YURI (Genome Informatics, 2011)
Elucidating protein-RNA interactions (PRIs) is important for understanding many cellular systems. We developed a PRI prediction method by using a rigid-body protein-RNA docking calculation with tertiary structure data. We evaluated this method by using 78 protein-RNA complex structures from the Protein Data Bank. We predicted the interactions for pairs in 78×78 combinations. Of these, 78 original complexes were defined as positive pairs, and the other 6,006 complexes were defined as negative pairs; then an F-measure value of 0.465 was obtained with our prediction system.